Thoughts On Interpellation And Intertextuality Among Facebook Cover Photos Of Four Major Political Parties As Visual Narratives During The Turkish General Election Of 2015 Campaign - Öngün, Erdem (The Turkish Online Journal of Design Art and Communication, 2015)
The main goal and interest in this paper is to explore how visual narrative processes function through single visual texts as cover photos on official Facebook pages of four major political parties ( Justice and Development Party ( JDP) a.k.a. AKP, Republican People’s Party ( RPP) a.k.a. CHP, Nationalist Movement Party (NMP) a.k.a. MHP and Peoples' Democratic Party (PDP) a.k.a. HDP ) represented in the Turkish Grand Assembly during general election campaign of 2015. The cover photos which illustrate appeal for vote and support are intended to communicate political competition and elicit political, ideological support and social responses. Using these cover photos on the Facebook profiles of these political parties as a sample, the paper reflects on intertexuality and interpellation processes and how these concepts contribute to further understanding the ways that engaged voters as viewers become participants and supporters in the narratives generated by these single visual texts. What narrative processes are in action during an encounter with a visual appeal for vote and support and how these processes function and how voters as viewing subjects might be able to exchange positions differently in relation to the visual texts appearing in the Facebook cover photos of the related political parties are the main questions to be answered and discussed in this study . Using a qualitative methodology, the study concludes with an overall comparative evaluation of the subject.
Keywords: Interpellation; Intertextuality; Visual Narrative; Social Media; Facebook; Political Discourse; Çağrı; Metinlerarasılılık; Görsel Anlatı; Sosyal Medya; Siyasi Söylem